Structural, optical and photoluminescence characterization of Mn-doped ZnO - Kabir, Abdenour; Nettour, Romeissa; Erdogmus, Ali; Kutlu, Oznur Dulger (SPRINGER HEIDELBERG, 2026)
In this work, experimental results of the effect of Mn ions incorporation on the structural, optical and luminescence properties of spray deposited ZnO thin films by varying the Mn molar ratio x in the precursor solution. For x = 0.00, XRD peaks revealed that the deposited film correspond to the hexagonal wurtzite structure of ZnO. For x = 0.02 and x = 0.04, the variation of crystalline parameters indicated the presence of compressive stress caused by the incorporation of Mn ions in ZnO. The stress relaxation, for x = 0.06, was accompanied by the appearance of other phases such as MnO2 and ZnMnO3 indicating the decomposition of ZnO phase. The crystallite size decreased from 72 to 35 nm as a function of Mn molar ratio confirming the loss of ZnO crystallinity. The disappearance of Zn-O-Zn bond related peaks in the ATR-FTIR spectrum, for x = 0.06, confirmed XRD results. As a function of Mn molar ratio x, the mean transmittance in the visible light region decreased from 80 to 60% while the band gap energy increased from 3.3 to 3.56 eV. The UV and NIR emission peaks, in PL spectra, decreased rapidly for x = 0.02 to disappear, for x = 0.04 and x = 0.06, with the appearance of violet, blue and blue-green emissions attributed to deep level defects. The presented results made the deposited films suitable for use in many applications such as energy-efficient lighting, photocatalytic water treatment, and spintronic devices for low-power computing.
Keywords: Mn-doped ZnO; Mn molar ratio; Compressive stress; Band gap energy; Deep level defects; THIN-FILMS; MAGNETIC-PROPERTIES; RAMAN-SCATTERING; ZINC-OXIDE; BAND-GAP; NANOPARTICLES; TEMPERATURE; GROWTH; LUMINESCENCE; SOLUBILITY; Materials Science; Physics